MEDIASI DALAM PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2016 - SARI, SEPTI WULAN (IAIN Tulungagung, 2017)
Mediation is an alternative dispute resolution in which the mediator function as a neutral mediator. With the mediation process is expected to solve the problems for the best solution. This current research employs library research or literature review which includes the systematic identification, and analysis of documents containing information related to the problems of the study. The approach used is normative juridical approach. In Indonesia, the court mediation is set out in the Supreme Court Regulation No. 1 of 2016. It is stated that the rules of mediation is as an alternative dispute resolution prior to the process of the case investigation. In addition, it is also explained in regard to the stages of pre and post-mediation process. The main goal of the rules of the Supreme Court above is to reduce the accumulation of the case in the court, and to gain a win-win solution.Keywords: Mediasi, Peraturan Mahkamah Agung